MHD nonlinear flow and heat transfer over a stretching porous surface of constant heat flux - Devi, Anjali; Ganga, B. (Computer Assisted Methods in Engineering and Science, 2008)
MHD nonlinear steady flow and heat transfer over a porous surface stretching with a power-law velocity and of constant heat flux is investigated . The governing nonlinear partial differential equations are reduced to nonlinear ordinary differential equations by using similarity transformation. As the presented solution method requires the magnetic field to vary in space in a specific manner, a special form for the variable magnetic field is chosen. Resulting equations are numerically solved by Runge-Kutta shooting method. Values of skin-friction and rate of heat transfer are obtained. The effect of magnetic field , stretching parameter, magnetic interaction parameter, suction parameter and Prandtl number over a flow fie ld and other physical quantities have been discussed in detail.